Evidence of persisting cognitive impairment in a case series of patients with locked-in syndrome. Issue 2 (23rd October 2008) - Rousseaux, M; Castelnot, E; Rigaux, P; Kozlowski, O; Danzé, F
Abstract : Objective: Previous research on cognition and locked-in syndrome (LIS) is limited to single case reports, and usually reported normality of performance. Here, cognitive disorders in a group of LIS patients are investigated, using a specific test relying only on a yes/no response indicated by eye movements or verbally. Methods: Nine patients with LIS resulting from brainstem stroke were compared with seven patients with frontal or frontotemporal lesions and 16 matching normal control subjects. The test comprised 19 subtests of perception (visual and auditory recognition), oral comprehension (identity, words and sentences), written comprehension (words and sentences), orientation (in time and place), immediate and delayed memories (verbal and visuo-spatial information), calculation and problem solving, and analysis of verbal logic. Results: LIS patients showed significant difficulties in auditory recognition (associative level), oral comprehension of complex sentences, delayed visuospatial memory, mental calculation and problem solving. Patients with hemispheric lesions were more severely impaired. Single case analysis revealed that four LIS patients showed cognitive disorders in at least three subtests. These disorders were not related to a specific localisation of lesions. Conclusions: Moderate and selective cognitive disorders can be observed in LIS patients. Systematic assessment is needed, because of their possible consequences for communication and rehabilitation protocols.